2022
DOI: 10.37606/publik.v9i3.345
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Online Customer Review, Word of Mouth, and Price Consciousness Terhadap Minat Beli Di Shopee

Abstract: The purpose was to determine the effect of Online Customer Review , Word Of Mouth, and Price Consciousness on Buying Interest  at Shopee. Type of research is quantitative research. The population in this study were active students of the 2018 and 2019 Faculty of Economics, Universitas Sarjanawiyata Tamansiswa totaling 1,383 then 120 samples. Sampling was carried out using the purposive sampling method. The data collection technique used was a survey method using a questionnaire. Then the data is processed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
(4 reference statements)
0
1
0
1
Order By: Relevance
“…Salah satu hambatan ketika berbelanja online ialah barang yang ingin dibeli tidak dapat dilihat secara langsung oleh customer. Pengalaman memuaskan atas produk yang pernah dibeli dapat meningkatkan keinginan konsumen untuk terus melakukan transaksi pada marketplace Shopee (Rinaja et al, 2022). Sebagai upaya menjaga kualitas produk yang dijual, Shopee memiliki pengukuran kualitas produk berdasarkan rating yang didapatkan, retur produk, serta keluhan konsumen.…”
Section: Pendahuluanunclassified
“…Salah satu hambatan ketika berbelanja online ialah barang yang ingin dibeli tidak dapat dilihat secara langsung oleh customer. Pengalaman memuaskan atas produk yang pernah dibeli dapat meningkatkan keinginan konsumen untuk terus melakukan transaksi pada marketplace Shopee (Rinaja et al, 2022). Sebagai upaya menjaga kualitas produk yang dijual, Shopee memiliki pengukuran kualitas produk berdasarkan rating yang didapatkan, retur produk, serta keluhan konsumen.…”
Section: Pendahuluanunclassified
“…Dzulqarnain in (Rinaja et al, 2022), customer service must meet product quality first before making a purchase transaction. (Nurfauzi et al, 2023)According to Gretzel & Yoo, they found that online reviews are the most important source of information for customers to generate customer purchase intentions.…”
Section: Definition Of Customer Servicementioning
confidence: 99%
“…Furthermore, (Rinaja et al, 2022) Trustworthiness, or whether information can be believed, is decided by the extent to which the source is perceived, to be honest, and trustworthy. Honesty is the expressing of one's ideas and sentiments about utilizing a product in an honest evaluation without manipulating, plagiarizing, or deceiving others for personal advantage.…”
Section: E-customers Reviewmentioning
confidence: 99%